2007
DOI: 10.1029/2006gl028525
|View full text |Cite
|
Sign up to set email alerts
|

East African soil erosion recorded in a 300 year old coral colony from Kenya

Abstract: Soil erosion is a key socio‐economic and environmental problem in Kenya, which has been poorly documented due to the lack of long, continuous records. Here we present Ba/Ca records from Porites corals from the Malindi coral reef documenting the flux of suspended sediment from the Sabaki River with a sub‐weekly resolution for the last 300 years. While sediment flux from the Sabaki River is almost constant between 1700 and 1900, a continuous rise in sediment flux is observed since 1900, first due to British sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 29 publications
3
95
1
Order By: Relevance
“…Studying fossil plants (e.g., pollen grains and macrofossils) allows scientists to reconstruct the history of forest loss [15], and river sediments to provide insights into erosion rates over several centuries [16]. Still, there is a paucity of data on early forest cover and practically no data on historical soil fertility in SSA (even from this last century).…”
Section: Time Horizonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying fossil plants (e.g., pollen grains and macrofossils) allows scientists to reconstruct the history of forest loss [15], and river sediments to provide insights into erosion rates over several centuries [16]. Still, there is a paucity of data on early forest cover and practically no data on historical soil fertility in SSA (even from this last century).…”
Section: Time Horizonsmentioning
confidence: 99%
“…In sum, these studies indicate that rates of soil degradation vary through time (are non-linear) and that not all indicators behave the same way. The longest study is the best example of this, which uses coral barium to calcium ratios from the Malindi reef to evaluate sediment transport (erosion) from the Sabaki river basin in Kenya [16]. Sediment flux was relatively low and consistent from 1700 to 1905, but rises after 1905, corresponding to the start of British settlement and land clearing, and periodic spikes that can be traced back to historical changes in land management.…”
Section: Longitudinal Studiesmentioning
confidence: 99%
“…Scleractinian corals can live for hundreds of years and continuously record changes in the marine environment in their aragonitic skeletons. Annual density banding in corals allows accurate time control on reconstructions (Knutson et al, 1972), and many studies have utilized corals for paleoclimatic and paleoenvironmental reconstruction, measuring stable isotopes (Dunbar et al, 1994;Cobb et al, 2003, Marion et al, 2005 and metals that substitute into the CaCO 3 matrix (Smith et al, 1979;Hanna and Muir, 1990;Bastidas and Garcia, 1999;Fallon et al, 2002;David, 2003;McCulloch et al, 2003;Ramos et al, 2004;Fleitmann et al, 2007;Lewis et al, 2007;Prouty et al, 2008). Although the coral calcification mechanism and therefore the exact pathway of metal substitution in the aragonite matrix are still under debate (Cohen and McConnaughey, 2003), empirical studies have shown that corals appear to faithfully record relative metal concentrations in the surrounding seawater (Runnalls and Coleman, 2003;Correge, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Suspended sediments (clays) carry adsorbed barium and other river-born trace elements that are desorbed in the low-salinity estuarine mixing zone and subsequently behave as conservative dissolved constituents of the ambient seawater in which the corals thrive (Sinclair and McCulloch 2004). Consequently, Ba/Ca and luminescence are used to reconstruct sediment and humic acid runoff, respectively in tropical catchments, where both have been shown to co-vary with the changing magnitude of precipitation and river flow (Fleitmann et al 2007). As Madagascar weather data are scarce (Dewar and Wallis 1999;Dewar and Richard 2007), novel spectral luminescence ratios and conventional luminescence intensities are paired with Ba/Ca to validate the method, supported by rainfall data from a nearby weather station.…”
Section: Introductionmentioning
confidence: 99%